Assessment of Local Health Worker Attitudes toward International Medical Volunteers in Low- and Middle-income Countries: A Global Survey - Bae, Crystal; Naik, Nehal; Misak, Monika; Barnes, Sean L.; Verceles, Avelino C.; Papali, Alfred; McCurdy, Michael T.; Losonczy, Lia I. (Journal of Epidemiology and Global Health, 2020)
Background International Medical Volunteers (IMVs) positively and negatively impact host countries, and the goals of their trips may not always align with the interests of the hosts in Low- and Middle-Income Countries (LMICs). We sought to better understand local physicians’ interest of hosting IMVs and what type of support they desired. Methods This study was a convenience sample survey-based needs assessment. The surveys were distributed to local physicians by 28 professional society groups in LMICs. Findings A total of 102 physicians from 51 countries completed the survey. Despite 61.8% participants having no experience with IMVs, 75% were interested in hosting them. Host physicians most desired clinical education (39%), research collaboration (18%), and Systems Development (11%). The most requested specialties were obstetrics and gynecology (25%) and emergency medicine (11%). Respondents considered public hospitals (62%) to be the most helpful clinical setting in which IMVs could work, and 3 months (47%) as the ideal length of stay. Respondents expressed interest in advertising the specific needs of the host country to potential IMVs (80%). Qualitative analyses suggested hosts wanted more training opportunities, inclusion of all stakeholders, culturally competent volunteers, and aid focused on subspecialty education, health policy, public health, and research. Conclusion Hosts desire more bidirectional clinical education and research capacity building than just direct clinical care. Importantly, cultural competence is key to a successful host partnership, potentially improved through IMV preparation. Finally, respondents want IMVs to ensure that they stay within their scope of practice and training.